2023
DOI: 10.1007/s40684-023-00529-0
|View full text |Cite
|
Sign up to set email alerts
|

Novel Use of Cellulose Based Biodegradable Nano Crystals in the Machining of PPS Composites: An Approach Towards Green Machining

Abstract: Because of their biodegradable and regenerative properties, cellulose nanocrystals derived primarily from naturally occurring cellulose fibers serve as a sustainable and environmentally beneficial material for most applications. Although these nanocrystals are inherently hydrophilic, they can be surface functionalized to suit a wide range of demanding requirements, such as those associated with the creation of high-performance nanocomposites in hydrophobic polymer matrices. Therefore, the present work deals wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…This can be explained by CNCbased nanofluids reducing the cutting temperature. In the literature, a machinability study using CNC-based nanofluids stated that different ratios of nanofluids played an effective role in reducing cutting temperatures [31]. Additionally, many studies reported that nanofluids prepared with different nanoparticles reduced the cutting temperature better than dry and MQL [38][39][40].…”
Section: Evaluation Of Cutting Temperature Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This can be explained by CNCbased nanofluids reducing the cutting temperature. In the literature, a machinability study using CNC-based nanofluids stated that different ratios of nanofluids played an effective role in reducing cutting temperatures [31]. Additionally, many studies reported that nanofluids prepared with different nanoparticles reduced the cutting temperature better than dry and MQL [38][39][40].…”
Section: Evaluation Of Cutting Temperature Resultsmentioning
confidence: 99%
“…Polymers 2023, 15, x FOR PEER REVIEW 7 of 17 based nanofluids stated that different ratios of nanofluids played an effective role in reducing cutting temperatures [31]. Additionally, many studies reported that nanofluids prepared with different nanoparticles reduced the cutting temperature better than dry and MQL [38][39][40].…”
Section: Evaluation Of Cutting Temperature Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These factors may cause rough textures, uneven surfaces, or other surface abnormalities, which may lower the overall aesthetic and functional qualities of the printed object [14]. Therefore, there is a need for a subtractive process such as machining to reduce the roughness [15].…”
Section: Introductionmentioning
confidence: 99%